1989
DOI: 10.4319/lo.1989.34.6.1004
|View full text |Cite
|
Sign up to set email alerts
|

Nitrification‐denitrification at the plant root‐sediment interface in wetlands

Abstract: Oxygen transport through the air spaces (aerenchyma tissue) of the stem and roots of aquatic macrophytes into the root zone supports nitrification of NH,+, with the NOJ-formed diffusing into the adjacent anaerobic zone where it undergoes #denitrification. To test this hypothesis, we conducted a growth chamber study to determine the transformation of applied 15NH,+-N to r5N, in the root zone of three aquatic macrophytes: rice (Oryza sativa L.), pickerel weed (Pontecferia cordata L.), and soft rush (Juncus e&us … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
236
0
4

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 480 publications
(246 citation statements)
references
References 35 publications
6
236
0
4
Order By: Relevance
“…Thomas et al. [68] mentioned that aerenchyma tissue plays a role in the emission of methane into the atmosphere through emergent wetland plants, supporting Reddy et al [69] who revealed the role of aerenchyma in releasing, to the atmosphere, N 2 and N 2 O produced by anaerobic denitrification of NO 3 in the wastewater. Brix [2] suggested that plants in CWs increase wildlife diversity, but we did not find any empirical study showing this effect or explaining this particular function.…”
Section: Microclimatic Conditionsmentioning
confidence: 78%
“…Thomas et al. [68] mentioned that aerenchyma tissue plays a role in the emission of methane into the atmosphere through emergent wetland plants, supporting Reddy et al [69] who revealed the role of aerenchyma in releasing, to the atmosphere, N 2 and N 2 O produced by anaerobic denitrification of NO 3 in the wastewater. Brix [2] suggested that plants in CWs increase wildlife diversity, but we did not find any empirical study showing this effect or explaining this particular function.…”
Section: Microclimatic Conditionsmentioning
confidence: 78%
“…Reddy et al (1989) observed that roots of rice (Oryza sativa) stimulated the coupled nitrificationdenitrification activity in waterlogged soils, and Caffrey and Kemp (1992) observed significant nitrification-denitrification activity in the rhizosphere of Potamogeton per$oliatusvegetated sediments. Christensen and Sorensen (1988) measured high rates of denitrification in the root zone of freshwater macrophyte Litorellu uniflora-vegetated sediments.…”
Section: Discussionmentioning
confidence: 99%
“…Aerenchymatous plants create an oxic-anoxic interface in the root zone by releasing oxygen into this zone [2,22]. The release of oxygen by the roots may stimulate nitrification [5,9,19] and, subsequently, denitrification after diffusion of nitrate into the reduced zone of the sediment. The decline of the aerenchymatous plant Phragmites australis (Cav.)…”
Section: Introductionmentioning
confidence: 99%